Optimizing ex vivo penetration tests via quantitative confocal Raman spectroscopy: Impact of incubation time, skin hydration, surfactant treatment and UVA irradiation on caffeine distribution - Steiner, Katja; Hübel, Pia; Srndic, Azra; Klang, Victoria (International journal of pharmaceutics, 2024)
[Display omitted] Ex vivo penetration tests are important tools in cosmetic and pharmaceutical research. However, variability of experimental setups is challenging when reviewing literature. Different skin models, pre-treatments and experimental parameters render comparison difficult. Thus, our aim was to conduct ex vivo penetration tests using caffeine in different setups with varying incubation conditions (ambient vs. Franz cells, infinite vs. finite dose). Additionally, the impact of skin pre-treatment with different aggressors (surfactants, UVA irradiation) should be considered. Possible synergistic barrier damage of surfactants and UVA irradiation should be explored. Analysis was conducted using quantitative confocal Raman spectroscopy. Results showed that incubation time and extensive hydration (20 h in Franz cells) had the greatest impact on penetration behavior. Additional irradiation after pre-treatment with oil-in-water nanoemulsions showed no strong impact on caffeine penetration in general, irrespective of surfactant type. However, in case of sodium lauryl ether sulfate, a trend towards enhanced values was observed due to irradiation (1.3-fold). This suggests cumulative skin barrier damage of irritant surfactants and UVA irradiation, potentially due to stratum corneum alterations. Further studies using different irradiation regimens are planned to confirm this hypothesis.